2006
DOI: 10.1017/s1041610205003017
|View full text |Cite
|
Sign up to set email alerts
|

Donepezil for negative signs in elderly patients with schizophrenia: an add-on, double-blind, crossover, placebo-controlled study

Abstract: Donepezil does not seem to improve negative signs and cognitive impairment in elderly patients with chronic schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…However, a small randomized, double-blind trial showed positive outcomes when galantamine was administered as an add-on therapy to antipsychotics (Schubert et al, 2006). To date, no positive outcomes have been observed with donepezil or rivastigmine (Mazeh et al, 2006;Sharma et al, 2006). In light of the present results, we conclude that the antagonism of KYNAinduced inhibition of ␣7* nAChRs may be causally related to the effectiveness of galantamine in schizophrenia and AD.…”
Section: Discussionmentioning
confidence: 45%
“…However, a small randomized, double-blind trial showed positive outcomes when galantamine was administered as an add-on therapy to antipsychotics (Schubert et al, 2006). To date, no positive outcomes have been observed with donepezil or rivastigmine (Mazeh et al, 2006;Sharma et al, 2006). In light of the present results, we conclude that the antagonism of KYNAinduced inhibition of ␣7* nAChRs may be causally related to the effectiveness of galantamine in schizophrenia and AD.…”
Section: Discussionmentioning
confidence: 45%
“…Twenty-four double-blind studies were found (table II): 5 with rivastigmine, [37,39,41,46,50] 13 with donepezil [31,[33][34][35][36]38,40,[43][44][45][47][48]52] and 6 with galantamine. [32,42,49,51,53,54] Fifteen of these studies did not show an improvement in cognition in schizophrenia, [31,[33][34][35][36][37][39][40][45][46]48,50,[52][53][54] six found cognitive improvement [32,[41][42][43]49,51] and three [38,44,47] found improvement in psychopathology.…”
Section: Qualitative Review Of the Literaturementioning
confidence: 99%
“…[32,42,49,51,53,54] Fifteen of these studies did not show an improvement in cognition in schizophrenia, [31,[33][34][35][36][37][39][40][45][46]48,50,[52][53][54] six found cognitive improvement [32,[41][42][43]49,51] and three [38,44,47] found improvement in psychopathology.…”
Section: Qualitative Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…These studies were all done using donepezil as a neuroleptic augmentation treatment. Some (Mazeh et al, 2006;Stryjer et al, 2003) were in elderly patients or patients with known comorbid dementia. Others were in a general population of stable schizophrenic patients (Friedman et al, 2002;Stryjer et al, 2004;Tugal et al, 2004).…”
Section: Despite Clear Effects Of Other Cholinergic Compounds Chomentioning
confidence: 99%